Ortho keratinized Odontogenic Cyst of Mandible: A Rare Case Report - Sargolzaei, Soudabeh; Mashhadi Abbas, Fatemeh; Hesami Moghadam, Leila; Jabbari, Sanaa; Zadsirjan, Saeideh (Journal of Dental School, 2019)
Objective: The Ortho keratinized Odontogenic Cyst (OOC) is a rare lesion originates from dental lamina and clinically, it may be mistaken for many other odontogenic cysts and Tumors. Microscopically, It should be distinguished from KCOT because of differences in biologic behavior and histologic features. Case: An interesting case of OOC arising in the edentulous mandibular right first premolar region of a 55-year-old woman is reported. Under the initial clinical diagnosis of a residual cyst, the excisional biopsy was performed. Because of detection of an orthokeratinized epithelium lining, a definite diagnosis of OOC was made. Conclusion: Microscopic examination is crucial for making the correct diagnosis of such lesions, therefore establishing patients' prognosis accurately.